Features characteristics of the sphenoid sinus disease in elderly patients. - Karpishchenko, S A; Arustamyan, I G; Stancheva, O A; Kaplun, D I (Advances in gerontology = Uspekhi gerontologii, 2023)
The aim of the study was to identify the features of diagnosis and treatment of sphenoid sinus diseases in patients over 60 years old. Clinical manifestations, results of endoscopic and radiological examination methods, and surgical intervention tactics were compared between elderly patients and younger patients (aged 18-59 years) who sought treatment for sphenoiditis in I.P.Pavlov Saint-Petersburg First State Medical University. The study analyzed 51 patients with isolated sphenoid sinus pathology, of which 9,8% were over 60 years old. The most common symptom in elderly patients was headache. Surgical treatment was required in 80% of patients over 60 years old. Endoscopic endonasal surgery of the sphenoid sinus can be safely performed by a specialized surgical team in patients over 60 years old with low anesthesiological risk. The results of our study showed that there were no statistically significant differences in the length of hospital stay between patients in both groups. This indicates that caring for elderly patients with sphenoid sinus pathology does not necessarily lead to prolonged hospitalization or increased economic burden on healthcare systems. Further research is needed to better understand the causes of the disease and to develop more effective approaches to the diagnosis, therapy, and prevention of sphenoid sinus pathology in elderly people.